Traffic Management in Addressing Congestion in Commercial Areas: A Case Study on Jl. Karanggetas, Cirebon City - Permana, Aditya; Wardani, Imron; Ramadhan, Hanif Nasrul; Bukhori, Bukhori (Indonesian Journal of Advanced Research, 2025)
Traffic congestion is a serious problem in commercial areas such as Jl. Karanggetas, Cirebon City, which affects the effectiveness of mobility, travel time, and community productivity. This study aims to identify the causes of traffic congestion and formulate traffic management solutions based on local needs. The method used is mixed-methods, combining secondary data such as Average Daily Traffic (LHR), road geometry, and side obstacles, as well as field surveys. The analysis was conducted based on the Indonesian Road Capacity Guidelines (PKJI) 2023, which is a national reference in evaluating road capacity and performance. The results showed that congestion is caused by illegal parking, loading and unloading activities during peak hours, and limited road capacity. The road level of service (LoS) is in the B and C categories, while the correlation between road user perception variables and congestion shows a weak relationship. Recommendations include the repositioning of parking zones, logistics timing, construction of angkot stops, and elimination of on-street parking to optimize traffic space capacity.